“... studying travelogues often becomes a journey...”: A. Y. Sorochan: Travel writing as literature. Monograph. Tver, “Alpha Press”, 2024, pp. 254. ISBN: 978‐5‐98721‐073‐4 - Váradi, Ferenc (Slavica, 2025)
The present review analyzes the monograph of A. Y. Sorochan, published in 2024. The author is a philologist, a professor at Tver State University who specializes in the history and theory of literature. He defended his doctoral dissertation titled “Motivation in the Russian Historical Novel of the 1830s–1840s”, which focuses on a unique combination of historical and literary approaches. This monograph is thematically close to Sorochan’s dissertation and consists of three parts: in the first the author speaks generally about travel literature; the second section is devoted to works of Russian literature; and the third section contains reviews of books on travel literature. In this critical article, the specificity of historical and imagological approaches in Sorochan’s work on travel literature is analyzed.